Development and experimental verification of a mathematical expression for the discharge rate of a semi-circular open channel - Liqin, Qu; Xinxiao, Yu; Juan, Xiao; Tingwu, Lei (International Journal of Agricultural and Biological Engineering, 2010)
Semi-circular open channel plays an important role in various applications and the measurement of its discharge is of interests. In this study, theoretical formulae for free overflow in a semi-circular channel are developed and presented for the discharge and wetted area relationship. The traditional discharge formulation and available experimental data are used to verify and validate the proposed relationships. The discharges calculated by using the proposed relationship show very good agreement with the experimental data sets. The results from this study supply the basis for circular weir development. Keywords: verification, discharge, open channel flow, weir, circular, wetted area, measurement DOI: 10.3965/j.issn.1934-6344.2010.03.019-026 Citation: Qu Liqin, Yu Xinxiao, Xiao Juan, Lei Tingwu. Development and experimental verification of a mathematical expression for the discharge rate of a semi-circular open channel. Int J Agric & Biol Eng, 2010; 3(3): 19<span style="line-height: 135%; font-family: